The frontal executive function in exercise addicts, moderate exercisers, and exercise avoiders. Issue 6 (22nd August 2016) - Ryu, Kwangmin; Kim, Yujin; Kwon, Minji; Kim, Hyunji; Kim, Jingu
Abstract : Background and Objectives: The purpose of this study was to compare the frontal executive functions of exercise addicts, moderate exercisers, and exercise avoiders. We hypothesized that exercise addicts and avoiders would have poorer executive functions compared to moderate exercisers. Methods: The Korean Exercise Addiction Scale was administrated to recruit participants. Electroencephalogram was recorded at the frontal scalp sites. Results: The results showed that P3 and N2 latencies were shorter in the exercise addiction group than in the avoidance and moderate groups. Exercise addicts and moderate exercisers showed faster response time than exercise avoiders. Discussion: P3 and N2 latencies and P3 and N2 amplitudes were discussed in terms of executive functions. Scientific Significance: This study showed that exercise addiction did not impair executive functions, but increased cognitive functioning. (Am J Addict 2016;25:466–471)